The Research and Develpoment of Javanese letter story book to improve reading skill Junior High School student in Magelang Regency. - Rahma, Hanif (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2015)
Reading Javanese letter is one of the basic competencies that must be mastered by students. The investigation shows that the students have not read the Javanese letter yet because they do not means to practice. The story book is the alternative media to attract students reading interest. The content of the story raised the theme of Magelang local wisdom supported with picture of illustrations. This research uses Research and Development (R&D) method. Data collection were collected by observation, interview, questionnaire, and documentation. The result shows that (1) both the teacher and student need the Javanese story book to improve their reading skill, (2) the book was compiled based on the result of the analysis of the teacher and students’ need (3) the validation result of the material expert scored 66, 2% and validation of media experts scored 73.3% categorized deserves to be tested on students. Keywords: Reading Javanese Letter, Story Book, Local Wisdom.